Pendampingan Pemanfaatan Limbah Kayu Desa Nagarawangi Kecamatan Rancakalong Kabupaten Sumedang - Leni Anggraeni; Hegel Reviana Vahlepi; Nurcahyadi Kusumah; Denis iswara; Ramada Yusup Passail; Riska Della Meilany; Restu Nugraha Prawira; Iwan Satriyo Nugroho (Politeknik Piksi Ganesha Indonesia, 2025)
In addition to the obstacles experienced by the people of Nagarawangi Village, the biggest problem that we highlighted to conduct a study in this village is the problem of environmental pollution due to wood production. So this is what motivated us to conduct observations and research on how the problem of environmental pollution can be cultivated into an alternative solution to increase additional income for the people of Nagarawangi Village. Namely by providing information on how to utilize wood waste into briquettes and bricks and as a mushroom medium.